Peritonitis due to complications of colonic diverticular disease: Operative tactic and results - Asiner, Boris (Cirugía del Uruguay, 1971)
The author's personal experience and results in peritóneal complications of the cliverticular colonic disease ( D.C.D.) are presented. A review is made of 30 cases selected · of a series of 230 patients presenting D.C.D. Preoperative diagnosis was correct in only 34 % of the cases. In 66 % other diagnosis were considered ( apendicitis, perforating ulcer, etc.). In all cases, however, operative diagnosis was established. The clasic perforative sindrome was absent in the majority of the cases, in which the symptomatology was progressive .Plain X Ray study is considered of main importance. The most frequently founded lesion was sigmoiditis with peritoneal extension. In oniy 3 % of cases perforation of one diverticul rended evident was present. Total mortality was 30 % . Various surgical procedures were utilized: primary resection in 6 cases with anastomosis in 2 of them, with good results. If the patient's conditions and with qualified surgeon and anaesthetict, primary resection is advisable. In other circunstances, differente kinds of colostomy and drainage should be used.